Construction of Economical Dip-Coater for the Fabrication of Hydrophobic Coatings: DOI : 10.48129/kjs.20811 - Venkatesh; A. Satyanarayana (Kuwait Journal of Science, 2023)
D.C. motors were considered the basic components for the construction and development of various nanotechnology research equipment due to their constant speed and high efficiency. Spin coater, dip-coater, and spray pyrolysis were a few among them which utilize the above-mentioned component for the production of thin-film coatings on the desired substrates. Conventional spin coater, dip-coater, and spray pyrolysis incur huge costs to purchase and install in research laboratories. In this letter, we report the economical construction of an Arduino-based dip-coater that uses a linear actuator consisting of a D.C. motor for the production of hydrophobic coatings. The dip and drawl rate of the as-constructed machine was estimated to be 3mm/sec and can be varied according to the requirement without any interferences of vibration. Further, the dip-coater was tested with TiO2 gel for the production of hydrophobic coatings on cotton fabrics. The coated fabrics were characterized using an x-ray diffractometer (XRD), which confirmed the presence of TiO2, and reflectance analysis using ultraviolet-visible and near-infrared spectroscopy (UV-VIS-NIR) on the coated fabric revealed a short increase in the visible spectra and an elongated increase in the infrared spectral region, and goniometer examination with a water droplet on the treated fabric revealed 137O contact and proved as a superhydrophobic coating.